HISTO-MORPHOMETRIC AND HISTOCHEMICAL COMPARATIVE STUDY OF THE LIVER IN COLLARD DOVE (Frivaldszky), RUDDY SHELDUCK (Pallas) IN SOUTH IRAQ. - Ahmed Adeb Muhamed; Eyhab.R.M.AL-Samawy; Ahmed Sami Jarad (Basrah Journal of Veterinary Research)
The results of present study showed that the liver of the Collard Dove and Ruddy Shelduck was covered by a thick connective tissue capsule, formed of collagen fibers and some reticular fibers. Hepatocytes were arranged as irregular anastomosing cords of two cells. The cords were separated from each other's by blood sinusoids. The hepatocytes were large polygonal cells with large rounded nuclei. The portal triads containing branches of hepatic artery, portal vein, bile duct and lymph vessels.